Medieval soundspace in the new digital leisure time media - Rodríguez, Gerardo Fabián (2015)
Videogames have become a very important cultural reference in our society, especially for the younger generation. The music, sound effects and noises that appear in them are examples of the general iconography we have of the past, in this case the medieval period. This study presents an approach to this phenomenon that represents one of the best examples to analyse the idea of what we think the Middle Ages was like, and, in particular, its soundscape.